PENGARUH SENAM HAMIL TERHADAP PENURUNAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III - Ira Kartika; Riska Rahmawati (Jurnal Sehat Masada, 2026)
Pregnancy brings about physical and psychological changes in expectant mothers. One common complaint among pregnant women—particularly those in the third trimester—is back pain. Engaging in light exercise, such as prenatal gymnastics, is one way to improve health during pregnancy. A preliminary survey at the Rajamandala Community Health Center (Puskesmas) revealed that 37 (41.1%) third-trimester pregnant women suffered from lower back pain. This study aimed to determine the effect of prenatal gymnastics on reducing lower back pain in third-trimester pregnant women. A pre-experimental research method utilizing a One-Group Pretest-Posttest Design was employed. The study involved 30 respondents who participated in prenatal gymnastics sessions twice a week for a period of two weeks. Pain levels were measured using the Numerical Rating Scale (NRS), and the data were analyzed using the Paired Sample T-test. The results showed that the mean pain score was 4 (moderate pain) prior to the exercises and dropped to 3 (mild pain) afterward. The analysis yielded a p-value of 0.001, indicating a significant effect of prenatal gymnastics on back pain. In conclusion, prenatal gymnastics has an effect on lower back pain in third-trimester pregnant women. It is recommended that pregnant women perform these exercises regularly to help alleviate lower back pain.